Effect of Tambora Leaf Extract (Ageratum Conyzoides) on the Healing of Abrasions in White Rats (Rattus Norvegicus) Galur Sprague Dawley - Ratih, Oktaviana; Nunung Herlina; Taufik Septiawan (CV. CENDIKIA JENIUS INDONESIA, 2025)
The tambora plant known as ground bile or bandotan in Central Kalimantan, has a variety of benefits due to the content of secondary metabolites such as alkaloids, flavonoids, phenols, and saponins. This study aims to determine the effect of tambora leaf extract (Ageratum Conyzoides) on abrasion wound healing in white rats (Rattus Norvegicus) Sprague Dawley. Extraction was carried out by maceration method using 96% ethanol solvent, and tested at three different concentrations of 0.25%, 0.5%, and 1%, as well as positive control using Bioplacenton ointment. To analyze the data, the Shapiro-Wilk normality test was used, and the p-value of 0.10 was greater than 0.05. The results showed that tambora leaf extract has antibacterial, antioxidant, and anti-inflammatory effects that support the healing process of blisters. Tambora leaf extract with a concentration of 1% (P3) proved to be the most effective in accelerating wound healing. The administration of tambora leaf extract (Ageratum Conyzoides) is proven to accelerate the healing of abrasions in Sprague Dawley white rats without causing infection or allergic reactions. Further research is recommended to compare with other ingredients, use different extract concentrations, and involve more samples. In addition, microscopic examination and clinical trials in humans also need to be carried out.